Assessment of susceptibility of creeping bentgrass cultivars to dollar spot, sensitivity of Kansas isolates of Sclerotinia homoeocarpa to demethylation inhibitor fungicides, and determination of mutations in beta-tubulin gene associated with resistance - Ostrander, Jesse Carl (Kansas State University, 2014)
Dollar spot disease of turfgrass, caused by the fungus Sclerotinia homoeocarpa, is the most economically important disease of intensively managed turfgrass such as creeping bentgrass (Agrostis stolonifera) in golf course fairways and putting greens. While several cultural management practices can lessen the severity of the disease, fungicide applications are necessary to manage the disease to acceptable levels. Host resistance is another avenue of improving the quality of turfgrass in response to dollar spot disease, but more information on cultivar susceptibility levels is necessary. Many fungicides are available to control dollar spot, but S. homoeocarpa has shown resistance to both demethylation inhibitor (DMI) and benzimidazole class fungicides. The objectives of this thesis were: (1) to evaluate 15 cultivars of creeping bentgrass under putting green and fairway management for both overall quality and disease severity of dollar spot in the presence and absence of fungicide applications; (2) to determine the sensitivity of Kansas S. homoeocarpa isolates to the DMI fungicides propiconazole, metconazole, tebuconazole, and triticonazole using in vitro mycelia growth assays; (3 to determine a best discriminatory dose concentration for each DMI fungicide that will provide for rapid testing of relative sensitivity, and (4) to sequence the entire β-tubulin gene of several resistant and sensitive isolates to determine mutations associated with resistance. There were differences in turfgrass quality among the 15 cultivars at putting green height but not fairway height. There were no significant differences in disease. In the fungicide resistance assays, the mean EC50 values were 0.0163, 0.038, 0.0612, and 0.0994 µg/ml for metconazole, propiconazole, tebuconazole, and triticonazole, respectively. Correlations were significant and positive for all pairwise comparisons of log10EC50 values. Regressions using discriminatory concentrations tested were significant. The most predictive concentrations were 0.01, 0.05, 0.05, and 0.10 µg/ml a.i, for metconazole, propiconazole, tebuconazole, and triticonazole, respectively. The entire β-tubulin gene was sequenced for four resistant and four sensitive isolates. The resistant isolates all harbored a substitution of alanine for glutamic acid at codon 198 (E198A).
Keywords: Dollarspot; Fungicide; Resistance; Turfgrass; Agriculture, General (0473); Horticulture (0471)